A bulletin from Greece: a health system under the pressure of the second COVID-19 wave. (3rd April 2021) - Siettos, Constantinos; Anastassopoulou, Cleo; Tsiamis, Constantinos; Vrioni, Georgia; Tsakris, Athanasios
ABSTRACT: In this article, we analyze the cascade of events since the beginning of the coronavirus disease 2019 (COVID-19) pandemic in Greece, with emphasis on the crisis' management so as to preserve the functionality of the national health system, which remains vulnerable due to the financial recession of the previous decade and chronic shortcomings . We compare and contrast the situation during the first and second epidemic wave. Understanding what possibly went wrong and when, is crucial . Such knowledge provides valuable guidance for the confrontation of the strong second wave that we are currently facing in Europe and other regions around the globe, as well as for the future waves that may follow.